Perhitungan Harga Pokok Produksi Menggunakan Metode Harga Pokok Proses Pada Pabrik Roti Morisa Tahun 2016 - Lilis Erma Andriyani; Petrus Maharani; Lilis Mardiana A. (Politeknik Negeri Semarang, 2018)
The final project aims to compare the result of calculation of the cost of production companies with the result of calculated cost of production with cost method process for production “Pabrik Roti Morisa” period on December 2016. This final project using interview and literature in data collecting method. While the method of collecting the data is used in final project is interview with owner of “Pabrik Roti Morisa” company, documentation, and literature review. Writing method in my final project using description and exposition method. The result of final project show that calculated cost of production using cost method process for production of “Pabrik Roti Morisa” is Rp 6.441,24 for production of Roti Tawar Casino and Rp 6.710,41 for production of Roti Manis Pisang Coklat . While the cost of production according to the company is Rp 6.125,00 for production of Roti Tawar Casino and for production of Roti Manis Pisang Coklat is Rp 7.000,00. This show that the calculated cost production with cost method process for production of Roti Tawar Casino more high Rp 316,24 than calculating company, and for production Roti Manis Pisang Coklat more low Rp 289,59 than calculating company